Personal Reflections on Finnish Matriculture: Transcript - Kailo, Kaarina (Matrix, 2026)
In this recorded interview, Dr. Kaarina Kailo shares her personal reflections about being a woman in Finland and Finnish matriculture. Transcript available (see PDF).LINK TO RECORDED VIDEO: Personal Reflections on Finnish Matriculture